Serum Antioxidative Enzymes Levels and Oxidative Stress Products in Children and Adolescents with Type I Diabetes Mellitus - Özlem Akgün; Nilgün Selçuk Duru; Murat Elevli (Galenos Yayinevi, 2018)
Aim:Type I diabetes mellitus (TIDM) is an oxidative stress condition in addition to being a chronic metabolic disease. In this study, our aim is to investigate the activity of antioxidative enzymes and the products of oxidative stress in children and adolescents with TIDM and compare the findings with those in healthy control subjects.Materials and Methods:The study enrolled 41 children and adolescents with TIDM (mean age 11.4±3.3 years; 21 female, 20 male) and 25 healthy subjects (mean age 11.3±3.1 years; 8 female, 17 male) with a similar age and gender distribution. Serum samples were obtained to detect the antioxidative enzymes of paraoxonase (PON), arylesterase (ARE), oxidation degradation products of malondialdehyde (MDA) and also zinc which acts as an antioxidant.Results:We found a significant decrease in PON activity and zinc levels in diabetics compared to the healthy controls (p=0.021; p<0.001, respectively). Zinc was negatively correlated to hemoglobin A1c (r=-0.317, p=0.049). MDA and ARE did not show a significant difference in the TIDM patients compared to the healthy subjects.Conclusion:Zinc level and PON activity were lower in diabetic children and adolescents. Further studies with larger samples are required to confirm their roles in the following and prognosis of TIDM.